Lipid Nanoparticles-Encapsulated YF4: A Potential Therapeutic Oral Peptide Delivery System for Hypertension Treatment - Zhao, Shengnan; Li, Jinhua; Zhou, Yang; Huang, Lingjing; Li, Yanfei; Xu, Juanjuan; Fu, Chunmei; Guo, Xia; Yang, Jian (Frontiers in Pharmacology, 2019)
Drugs are administered orally in the clinical treatment of hypertension. Antihypertensive peptides have excellent angiotensin converting enzyme inhibitors activity in vitro. However, the poor oral bioavailability and therapeutic effect of antihypertensive peptides were mainly caused by rapid degradation in gastrointestinal and the short circulation time in blood, which remain to be further optimized. Therefore, the novel oral peptide delivery system is urged to improve the oral absorption and efficacy of peptide drugs. In this work, Tyr-Gly-Leu-Phe (YF4)-loaded lipid nanoparticles (YF4-LNPs) combined the advantages of polymer nanoparticles and liposomes were developed, which could greatly enhance the oral bioavailability and ameliorate the sustained release of peptide drug. YF4 loaded nanoparticles (YF4-NPs) were firstly prepared by a double-emulsion internal phase/organic phase/external phase (W1/O/W2) solvent evaporation method. YF4-NPs were further coated by membrane hydration-ultrasonic dispersion method to obtain the YF4-LNPs. The optimal YF4-LNPs showed a small particle size of 227.3 ± 3.8 nm, zeta potential of -7.27± 0.85 mV and high entrapment efficiency of 90.28 ± 1.23%. Transmission electronic microscopy analysis showed that the core-shell lipid nanoparticles were spherical shapes with an apparent lipid bilayer on the surface. Differential scanning calorimetry further proved that YF4 was successfully entrapped into YF4-LNPs. The optimal preparation of YF4-LNPs exhibited sustained release of YF4 in vitro and a 5 days long-term antihypertensive effect in vivo. In summary, the lipid nanoparticles for oral antihypertensive peptide delivery were successfully constructed, which might have a promising future for hypertension treatment.